Callousness and meanness traits are associated with increased N2 amplitude in a community sample of adolescents and adults. (27th July 2019) - Prata, C.; Pasion, R.; Fernandes, M.; Almeida, R.; Pereira, M.R.; Mazer, P.; Barbosa, F.
Highlights: Unemotionality traits (CU factor) predicted reduced N2 amplitude in adolescents. Remorselessness traits (CU factor) predicted reduced P3 amplitude in adolescents. Callousness traits (CU factor) predicted increased N2 amplitude in adolescents. Meanness traits also predicted increased N2 amplitude in adults. Callousness traits as a specific developmental root of meanness. Abstract: The lack of consistent findings in the research field of psychopathy unveils the heterogeneity of this personality structure and, therefore, a dissociation of its phenotypic components is a promising venue to conciliate paradoxical results. The current study aims to assess the dissociable effects of psychopathic traits on N2 and P3 modulation, while analyzing the stability of some endophenotypic processes across development. A sample of adolescents ( n = 33) and adults ( n = 31) completed, respectively, the Youth Psychopathy Inventory and the Triarchic Psychopathy Measure and performed the same Go/No-Go task during an EEG recording. For adolescents, the unemotionality and remorselessness subdimensions of the callous-unemotional (CU) factor predicted, respectively, reduced N2 and P3 amplitudes. This suggests impaired inhibitory control in both subdimensions of the broad CU factor. However, the callousness subdimension of the CU factor predicted increased N2 amplitude. This pattern of findings was also observed for meanness in adults, which leads to the hypothesis that callousness traits may be a specific precursor of meanness.